Dual photonic-phononic nanocavities for tailoring the acousto-optic interaction - N. Papanikolaou; E. Almpanis; G. Gantzounis; A. Christofi; L. Athanasekos; N. Stefanou (Microelecronic Engineering, 2016)
We report on the influence of elastic waves on the optical response and light emission in simultaneously photonic and phononic resonant cavities. Elastic waves couple with light through the acousto-optic interaction. Concurrent control of both light and sound through simultaneously photonic–phononic, often called phoxonic, band-gap structures is intended to advance both our understanding as well as our ability to manipulate light with sound and vise versa. In particular, co-localization of light and sound in phoxonic cavities could trigger nonlinear absorption and emission processes and lead to enhanced acousto-optic effects. We review our recent work on sound-controlled optical response and light emission in phoxonic cavities and investigate the limits of validity of the photoelastic model that describes light–sound interaction to first-order approximation. Moreover we present some preliminary results on silicon nitride nanobeam phoxonic devices.